ChemInform Abstract: Regioselective Cross‐Coupling of Allylboronic Acid Pinacol Ester Derivatives with Aryl Halides via Pd‐PEPPSI‐IPent. Issue 14 (20th March 2013) - Farmer, Jennifer L.; Hunter, Howard N.; Organ, Michael G.
Abstract This highly reliable protocol for selective α‐allylation of aromatic halides relies on the utilization of the sterically bulky catalyst PPI.